STRATEGIC ELEMENTS OF ORGANIZATIONAL KNOWLEDGE MANAGEMENT FOR IN-NOVATION CASE: AGROMETEOROLOGY NETWORK - Olivares, Barlin Orlando (2016)
This teaching experience seeks to propose an organizational knowledge management model for the training program developed by the Agrometeorology Department of the National Institute for Agricultural Research (INAI, in Spanish) of the State of Anzoátegui, Venezuela. The problem solution protocol deriving from the application of learning cycles, TADIR (Translation, Analysis, Design, Implementation and Revision), was used. An array of different ways to promote activities, tasks, results, and products generated by the project was established before, during and after the execution in an easy and complete manner. The population was also made aware of the advantages of agrometeorology and its importance for the agricultural development of the country. The results of this research can be made directly or indirectly available to the same organization or any others who wish to take the challenge of contributing to the transformation process the country is undergoing.